Microbial and metabolomic insights into the bovine lipometabolic responses of rumen and mammary gland to zymolytic small peptide supplementation - Liu, En; Xiao, Weiwei; Pu, Qijian; Xu, Lanjiao; Wang, Long; Mao, Kang; Hong, Wei; Qu, Mingren; Xue, Fuguang (Frontiers in Veterinary Science, 2022)
Small peptides provide the easy utilized nitrogen for rumen microbial and promote acetate generation for milk fat synthesis. However, impacts of peptide supplement on lipometabolic processes were still unclear. Therefore, total of 800 multiparous dairy herds (with the average live weight of 667.6±39.4kg, the average lactation of 89.3±18.8d, and the average calving parities of 2.76±0.47) were randomly allocated into the control (CON) and the small peptide supplement (100g/d for each cow) treatments (SP), respectively. All cows were conducted for a 35d-long feeding procedure which included a 7-days-long pre-treatment and 28-days-long treatment test. Dry matter intake (DMI) was recorded every day and calculated by the deviation between the supply and residue, while the daily milk production was automatically recorded through the rotory milking facilities. Milk samples were collected from each replicate at the last day, followed by the milk quality and milk lipid composition measurement. Rumen fluid samples were collected at the last day through oesophageal tubing at 3h after morning feeding for the determination of the underlying mechanism of small peptide on lipid metabolism through the measurement of rumen lipometabolic related metabolites and rumen bacterial communities. Results indicated that dry matter intake showed an increasing trend while milk production and the milk fat content remarkably increased after SP supplement (P<0.05). Further detailed detection showed the mainly increased milk composition focused on monounsaturated fatty acid (MUFA) and polyunsaturated fatty acid (PUFA). Acetate generating related microbe such as Acetitomaculum, Bifidobacterium, Succiniclasticum, and Succinivibrio, and butyrate generating related microbes including Shuttleworthia, and Saccharofermentans significantly proliferated, which causatively brought the increased ruminal content of acetate, isobutyrate, and butyrate after SP supplement(P<0.05) compared with CON. Lipometabolic metabolites such as phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylinositol (PI), phosphatidylserine (PS), triacylglycerol (TG), and Acetyl-CoA also significantly increased after SP supplement. In summary, small peptide supplement help increased milk fat content through the proliferation of rumen bacterial communities, which provided more acetate and butyrate for milk fat synthesis combined with the promotion of ruminal lipometabolism.